Angiotensin-converting enzyme insertion/deletion gene polymorphism and Henoch-Schonlein purpura nephritis risk in children: a meta-analysis - Yan, Pan; Xu, Song (Polish Journal of Pathology, 2023)
It has been demonstrated in many studies that angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism is related to Henoch-Schonlein purpura nephritis (HSPN) risk in children. However, this conclusion remains controversial. In this study, we systemically retrieved relevant studies in electronic databases such as PUBMED, CNKI, and EMBASE followed by calculation of odds ratios (OR) with 95% confidence intervals (CI). In addition, meta-package in STATA version 12.0 was used. Angiotensin-converting enzyme I/D polymorphism was related to HSPN susceptibility in children (D vs. I: OR 1.47, 95% CI: 1.13–1.93; DD vs. II: OR 2.29, 95% CI: 1.29–4.07; DI vs. II: OR 1.10, 95% CI: 0.82–1.48; dominant model: OR 1.44, 95% CI: 1.09–1.89; recessive model: OR 2.26, 95% CI: 1.67–3.06). In addition, subgroup analysis stratified according to ethnicity indicated a significant relationship between this polymorphism and HSPN susceptibility among Asians and Caucasians. The data extracted from HaploReg indicated that ACE I/D polymorphism was not in linkage disequilibrium with other variants in the ACE gene. The research shows that ACE I/D polymorphism is related to HSPN susceptibility in children.